The Complex Conformational Dynamics of Neuronal Calcium Sensor-1: A Single Molecule Perspective - Choudhary, Dhawal; Kragelund, Birthe B.; Heidarsson, Pétur O.; Cecconi, Ciro (Frontiers in Molecular Neuroscience, 2018)
The human neuronal calcium sensor-1 (NCS-1) is a multispecific two-domain EF-hand protein expressed predominantly in neurons and is a member of the neuronal calcium sensor (NCS) protein family. Structure-function relationships of NCS-1 have been extensively studied showing that conformational dynamics linked to diverse ion-binding is important to its function. NCS-1 transduces Ca+2 changes in neurons and is linked to a wide range of neuronal functions such as regulation of neurotransmitter release, voltage-gated Ca+2 channels and neuronal outgrowth. Dysfunction of NCS-1 can be deleterious to cells and has been linked to serious neuronal disorders like autism. Here we review recent studies describing at single molecule level the structural and mechanistic details of the folding and misfolding processes of NCS-1. By manipulating one molecule at a time with optical tweezers, the conformational equilibria of the Ca+2-bound, Mg+2-bound and apo states of NCS-1 were investigated revealing a complex folding mechanism underlain by a rugged and multidimensional energy landscape. The molecular rearrangements that NCS-1 undergoes to transit from one conformation to another and the energetics of these reactions are tightly regulated by the binding of divalent ions (Ca+2 and Mg+2) to its EF-hands. At pathologically high Ca2+ concentrations the protein sometimes follows non-productive misfolding pathways leading to kinetically trapped and potentially harmful misfolded conformations. We discuss the significance of these misfolding events as well as the role of inter-domain interactions in shaping the energy landscape and ultimately the biological function of NCS-1.